Role of tutorial classes and full day schooling on self-reported age of myopia onset: findings in a sample of Argentinian adults - Lança, Carla (2022)
Purpose: To investigate the effect of tutorial classes and schooling schedules in childhood on the age of myopia onset. Methods: Refractive data for subjects ≥18 years of age were collected from 8 dispensing opticians or refractive ophthalmologists' offices in Argentina. Age of myopia onset, spherical equivalent (SE), and risk factors were determined using questionnaires. Multiple linear regression models were applied to assess possible factors associated with the age of myopia onset or final adult SE. Results: A total of 274 adults (61.3% females) with myopia between -0.50 and -6.00 D were included. The mean age was 36.9 ± 14.5 years. The mean adult SE was -2.95 ± 1.45 D, and the mean age of myopia onset was 14.2 ± 5.4 years. Subjects that attended after-school tutorial classes (β = -2.23; P = 0.005) or a full day schedule in primary school (β = -1.07; P = 0.035) or that spent more time on near work (β = -0.70; P = 0.010) in childhood, had younger age of myopia onset. Conclusions: In our study cohort, adults that had attended tutorial classes and/or full-day schooling during childhood had a younger age of myopia onset.